2014
DOI: 10.1103/physrevc.89.014614
|View full text |Cite
|
Sign up to set email alerts
|

Shell effects in damped collisions ofSr88withYb176at the Coulomb barrier energy

Abstract: This work is a study of the influence of shell effects on the formation of binary fragments in damped collision. We have investigated binary reaction channels of the composite system with Z = 108 produced in the reaction 88 Sr+ 176 Yb at an energy slightly above the Bass barrier (E c.m. /E Bass = 1.03). Reaction products were detected by using the two-arm time-of-flight spectrometer CORSET at the K130 cyclotron of the Department of Physics, University of Jyväskylä. The mass-energy distribution of primary binar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…This behavior indicates the effect of the quantum shells of 208 Pb. We note that influence of quantum shells in QF processes has been routinely observed experimentally [66][67][68][69][70][71][72] and discussed theoretically [10, 12, 28-30, 57, 73-76].…”
Section: Tdhf Resultsmentioning
confidence: 76%
“…This behavior indicates the effect of the quantum shells of 208 Pb. We note that influence of quantum shells in QF processes has been routinely observed experimentally [66][67][68][69][70][71][72] and discussed theoretically [10, 12, 28-30, 57, 73-76].…”
Section: Tdhf Resultsmentioning
confidence: 76%
“…Quasifission occurs at a considerably shorter time-scale than fusion-fission [11,12,13] and is characterized by reaction fragments that differ significantly in mass from the original target/projectile nuclei. Quasifission for being one of the primary reaction mechanism that limits the formation of superheavy nuclei [14,15,16] has been the subject of intense experimental studies of [12,13,17,18,19,20,21,22,23,24,11,25,26,27,28,29,30,24,31,32,33,34]. Studies have also shown a strong impact of the entrance channel characteristics, including deformation [18,35,19,36,22,23,37] and shell structure [28] of the reactants.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown a strong impact of the entrance channel characteristics, including deformation [18,35,19,36,22,23,37] and shell structure [28] of the reactants. The final phase of the dynamics is also impacted by the fissility of the composite system [26,29], its neutron richness [32], and by shell effects in the exit channel [12,13,20,23,38,39,40,24,31]. A number of theoretical approaches have been developed that describe the quasifission in terms of multi-nucleon transfer (MNT) processes [41,42,43,44,45,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…havior may be due to the fact that Zr isotopes (Z = 40) in the mass range 100 − 112 are strongly bound with a large prolate deformation around β 2 = 0.42 [48][49][50]. Due to shell effects, these configurations may be energetically favorable during the QF dynamics [16,17,19]. A similar effect is observed in TDHF calculations of collisions with the tip of 238 U which favors the formation of fragments in the vicinity of the doubly magic 208 Pb nucleus [39].…”
Section: Pb Targets Ormentioning
confidence: 99%
“…Many experimental studies have been performed to understand the mechanisms at play in the quasi-fission process since its discovery [11][12][13][14][15][16][17][18][19]. Various theoretical models [20][21][22] have also been developed to help in the interpretation of these experimental data.…”
Section: Pb Targets Ormentioning
confidence: 99%